Bifurcation of the state of equilibrium in the system of nonlinear parabolic equations with transformed argument - Klevchuk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider a system of nonlinear parabolic equations with transformed argument and prove the existence of integral manifolds. We investigate the bifurcation of an invariant torus from the state of equilibrium.